2007
DOI: 10.1111/j.1095-8649.2007.01305.x
|View full text |Cite
|
Sign up to set email alerts
|

The influence of temperature during early life on phenotypic expression at later ontogenetic stages in sea bass

Abstract: To exam whether the temperature experienced by fishes at early developmental stages can influence their phenotype at subsequent stages, the model species used, European sea bass Dicentrarchus labrax was subjected to water temperatures of 15 or 20°C during the half-epiboly stage until the metamorphosis. Meristic and morphometric characters at three different stages, well after the end of the thermal treatments, were explored. Body shape and most of the meristic characters were significantly affected by the envi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
83
1
16

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(109 citation statements)
references
References 71 publications
9
83
1
16
Order By: Relevance
“…The fact that the examined morphometric characters do not significantly vary among the four temperature groups leads us to conclude that there is no such correlation between these size-related values and the observed differentiation of swimming performance. On the other hand, unpublished results of our team indicate that zebrafish grown in different temperatures tend to differ in both body shape and meristic character count, which is in agreement with the results of Georgakopoulou et al (2007). It is logical to assume therefore that it is a combination of those characters (body shape in general) and it's variation among the different temperature regimes rather than the effect of a single one that eventually influences the swimming ability of a fish.…”
Section: Discussionsupporting
confidence: 77%
See 2 more Smart Citations
“…The fact that the examined morphometric characters do not significantly vary among the four temperature groups leads us to conclude that there is no such correlation between these size-related values and the observed differentiation of swimming performance. On the other hand, unpublished results of our team indicate that zebrafish grown in different temperatures tend to differ in both body shape and meristic character count, which is in agreement with the results of Georgakopoulou et al (2007). It is logical to assume therefore that it is a combination of those characters (body shape in general) and it's variation among the different temperature regimes rather than the effect of a single one that eventually influences the swimming ability of a fish.…”
Section: Discussionsupporting
confidence: 77%
“…Georgakopoulou et al (2007), concluded that European sea bass juveniles reared in 15°C had more slender bodies than the ones reared in 20°C, a fact that could explain the higher swimming performance of the former as observed by Koumoundouros et al (2009).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In Zebra fish (Danio rerio) for instances, raising of juveniles under four different developmental temperatures resulted to highly variable phenotypes (Sfakianakis et al 2011). A similar study by Georgakopoulou et al (2007) on European seabass (Dicentrarchus labrax, L) showed that samples reared under lower temperatures (15°C) were more slender than those reared under higher temperature (20°C). Even though no studies have been carried out to establish the effect of water pH on fish shape, extreme changes in water pH have been reported to cause fish deaths by altering other aspects of water chemistry, for instance increase in pH increases toxicity of ammonia (Schofield 1976;Wurts and Durborow 1992).…”
Section: Introductionmentioning
confidence: 63%
“…Nevertheless, no controlled laboratory experiment has yet been reported on the potential role of environmental factors in formation of scale shape. according to the results on other morphological features [9,20,21], it is very likely, however, that scale shape might also vary along environmental gradients.…”
Section: Introductionmentioning
confidence: 91%